Defective TiO2 for photocatalytic CO2 conversion to fuels and chemicals. Issue 12 (24th February 2021) - Rawool, Sushma A.; Yadav, Kishan K.; Polshettiwar, Vivek
Abstract : This review discusses photocatalytic CO2 conversion using defective TiO2, with emphasis on the mechanism, the role of defects on CO2 adsorption–activation and product selectivity, as well as challenges of defective TiO2 to produce solar fuels. Abstract : Photocatalytic conversion of CO2 into fuels and valuable chemicals using solar energy is a promising technology to combat climate change and meet the growing energy demand. Extensive effort is going on for the development of a photocatalyst with desirable optical, surface and electronic properties. This review article discusses recent development in the field of photocatalytic CO2 conversion using defective TiO2 . It specifically focuses on the different synthesis methodologies adapted to generate the defects and their impact on the chemical, optical and surface properties of TiO2 and, thus, photocatalytic CO2 conversion. It also encompasses theoretical investigations performed to understand the role of defects in adsorption and activation of CO2 and identify the mechanistic pathway which governs the formation and selectivity of different products. It is divided into three parts: (i) general mechanism and thermodynamic criteria for defective TiO2 catalyzed CO2 conversion, (ii) theoretical investigation on the role of defects in the CO2 adsorption–activation and mechanism responsible for the formation and selectivity of different products, and (iii) the effect of variation of physicochemical properties of defective TiO2 synthesized using different methods on the photocatalytic conversion of CO2 . The review also discusses the limitations and the challenges of defective TiO2 photocatalysts that need to be overcome for the production of sustainable fuel utilizing solar energy.